Optimization of Microwave-Assisted Extraction Method for Increased Extraction Yield and Total Phenol Content from Moringa Leaves (Moringa oleifera Lam.) var. PKM 1 - Sandeep Gunalan; Arumugam Thangaiah; Janavi Gnanaguru Janaki; Anitha Thiyagarajan; Senthil Kuppusamy; Lakshmanan Arunachalam (Advances in Agriculture)
Moringa (Moringa oleifera Lam.) is an incredible plant with a storehouse of essential nutrients such as proteins, vitamins, minerals, and phytochemicals such as phenols, flavonoids, glycosides, and sterioids. From the qualitative screening, phytochemical was highly present in hydroethanolic extracts. Through hydroethanolic extraction, the recovery of these biomolecules could be achieved throughadvanced novel extraction methods such as microwave-assisted extraction. The main aim of this experimental trial is to optimize three independent factors including power (500 W–700 W), temperature (30°C–50°C), and extraction time (20 min–40 min) consisting of two levels of dependent variables such as extraction yield (EY) and total phenol content (TPC) using Response Surface Methodology (RSM) constructed by Central Composite Design (CCD) with 20 trial runs. The optimized extraction method recorded 14.64 to 17.65% of extraction yield and 63.36 to 76.40 mg GA/gram of total phenol content. As a result of the optimization of microwave-assisted extraction, the recovery of biomolecules from the dried moringa leaves is achieved by increasing the extraction temperature and time with the microwave power of the instrument.